18F-FDG PET/CT in the diagnosis and treatment of atypical extensive skin lesions in extranodal natural killer/T-cell lymphoma, nasal type: a case report - Liu, Xu-Sheng; Pei, Zhi-Jun (Frontiers in Oncology, 2025)
We report a case of a 60-year-old man who developed scattered erythema and papules on his left upper limb without any apparent cause 6 months ago. Initially, the patient underwent evaluations for various dermatological conditions, including eczema and psoriasis, while also being assessed for potential malignancies such as cutaneous lymphoma or sarcoidosis, but no definitive diagnosis was made. Over time, the patient’s symptoms progressed, presenting as generalized erythema, papules, localized itching, and pain. A histopathological examination of the lesions diagnosed it as extranodal NK/T-cell lymphoma, nasal type (ENKTCL-NT). Subsequently, the patient was referred for staging via 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT), which revealed a widespread pattern of metabolically active lesions primarily affecting the skin and subcutaneous tissue of the limbs and buttocks. The patient received sequential treatment with P-GEMOX (gemcitabine, oxaliplatin, and pegaspargase) and underwent clinical examination and follow-up whole-body 18F-FDG PET/CT after six treatment cycles. The post-treatment PET/CT showed no abnormal 18F-FDG uptake in the nasal cavity or skin, confirming clinical complete remission. Our case highlights the significant role of 18F-FDG PET/CT in clinical practice for initial staging and treatment response assessment of ENKTCL-NT.